设A,B为随机事件,P(B)>0,则()
A: P(A∪B)≥P(A)+P(B)
B: P(A—B)≥P(A)—P(B)
C: P(AB)≥P(A)P(B)
D: P(A|B)≥
E:
A: P(A∪B)≥P(A)+P(B)
B: P(A—B)≥P(A)—P(B)
C: P(AB)≥P(A)P(B)
D: P(A|B)≥
E:
举一反三
- 设A,B为随机事件,P(A)>0,P(A|B)=1,则必有 A: P(A∪B)=P(A) B: AB C: P(A)=P(B) D: P(AB)=P(A)
- 设A,B为随机事件,则P(A-B)= A: P(A)-P(B) B: P(A)-P(AB) C: P(A)-P(B)+ P(AB) D: P(A)+P(B)- P(AB)
- 设A,B为随机事件,P(A)>0,P(A|B)=1,则必有() A: P(A∪B)=P(A) B: A∈B C: P(A)=P(B) D: P(AB)=P(A)
- 设A,B为随机事件,P(A)>0,P(A|B)=1,则必有() A: P(A∪B)=P(A) B: A∈B C: P(A)=P(B) D: P(AB)=P(A)
- 设A,B为随机事件,P(A)>0,P(A|B)=1,则必有() A: P(A∪B)=P(A) B: A∈B C: P(A)=P(B) D: P(AB)=P(A)